Nonmigrating tidal activity related to the sudden stratospheric warming in the Arctic winter of 2003/2004 - D. Pancheva; P. Mukhtarov; B. Andonov (Annales Geophysicae, 2009)
This paper is focused on the nonmigrating tidal activity seen in the SABER/TIMED temperatures that is related to the major sudden stratospheric warming (SSW) taking place in the Arctic winter of 2003/2004. The emphasis is on the nonmigrating diurnal tides observed in the stratosphere and lower mesosphere which is usually accepted to be insignificant in comparison with that in the upper mesosphere and thermosphere. By using different independent spectral methods we found a significant amplification in December–January of the following nonmigrating 24-h tides: zonally symmetric ( s =0), eastward propagating with zonal wavenumber 1 (E1), and westward propagating with zonal wavenumbers 2 and 3 (W2 and W3) tides. It has been found that the double peak nonmigrating tidal amplifications located in the stratosphere (~40 km) and in the lower mesosphere (~70 km) are a consequence of the maintained hydrostatic relation. By detailed comparison of the evolution and spatial structure of the nonmigrating diurnal tides with those of the migrating diurnal tide and stationary planetary waves (SPWs) evidence for a SPW-migrating tide interaction as a source of nonmigrating tides has been presented. Therefore, the nonmigrating 24-h tides turn out to be an important component of the middle atmosphere dynamics during the major SSW in the Arctic winter of 2003/2004.